Invasion of the energy monsters: a family board game about energy consumption - Banerjee, Amartya; Horn, Michael S.; Davis, Pryce (2016)
We present Invasion of the Energy Monsters, a board game that attempts to highlight the role of family practices in household energy consumption. While household energy management activities — such as controlling heating and cooling systems — tend to be adult centric, we believe that children and adolescents have a meaningful role to play in helping their families move toward more sustainable ways of living. To that end, Energy Monsters has been designed to scaffold interactions between family members and encourage conversations about electricity consumption and waste. In this paper we provide an overview of our current design and a brief summary of results from our playtesting sessions with five families, and a description of versions that are under development.